HPV vaccine recommendation profiles among a national network of pediatric practitioners: understanding contributors to parental vaccine hesitancy and acceptance - Hopfer, Suellen (Hum Vaccin Immunother, 2019)
Background: Practitioner communication is one of the most important influences and predictors of HPV vaccination uptake. The objective of this study was to conduct a latent class analysis characterizing pediatric practitioner HPV recommendation patterns. Methods: Pediatric practitioners of the American Academy of Pediatrics’ (AAP) Pediatric Research in Office Settings (PROS) national network completed an online survey where they were presented with 5 hypothetical vignettes of well child visits and responded to questions. Questions asked about their use of communication strategies, assessments about the adolescent patient becoming sexually active in the next 2 years for decision-making about HPV vaccine recommendation, and peer norms. Latent class analysis characterized practitioner subgroups based on their response patterns to 10 survey questions. Multinomial logistic regression examined practitioner characteristics associated with each profile. Results: Among 470 respondents, we identified three distinct practitioner HPV vaccine recommendation profiles: (1) Engagers (52%) followed national age-based guidelines, strongly recommended HPV vaccination, and perceived peers as strongly recommending; (2) Protocol Followers (20%) also strongly recommended HPV vaccination, but were less likely to engage families in a discussion about benefits; and (3) Ambivalent HPV Vaccine Recommenders (28%) delayed or did not recommend HPV vaccination and were more likely to use judgment about whether adolescents will become sexually active in the next two years. Practicing in a suburban setting was associated with twice the odds of being an Ambivalent Recommender relative to being an Engager (OR = 2.2; 95% CI:1.1–4.1). Conclusions: Findings underscore the importance of continued efforts to bolster practitioner adoption of evidence-based approaches to HPV vaccine recommendation especially among Ambivalent Recommenders.